Application of Ferriferous Oxide Modified by Chitosan in Gene Delivery. (27th December 2012) - Kuang, Yu; Yuan, Tun; Zhang, Zhongwei; Li, Mingyuan; Yang, Yuan
Abstract : New approaches to improve the traditional gene carriers are still required. Here we explore Fe3 O4 modified with degradable polymers that enhances gene delivery and target delivery using permanent magnetic field. Two magnetic Fe3 O4 nanoparticles coated with chitosan (CTS) and polyethylene glycol (PEG) were synthesized by means of controlled chemical coprecipitation. Plasmid pEGFP was encapsulated as a reported gene. The ferriferous oxide complexes were approximately spherical; surface charge of CTS-Fe3 O4 and PEG-Fe3 O4 was about 20 mv and 0 mv, respectively. The controlled release of DNA from the CTS-Fe3 O4 nanoparticles was observed. Concurrently, a desired Fe3 O4 concentration of less than 2 mM was verified as safe by means of a cytotoxicity test in vitro. Presence of the permanent magnetic field significantly increased the transfection efficiency. Furthermore, the passive target property and safety of magnetic nanoparticles were also demonstrated in an in vivo test. The novel gene delivery system was proved to be an effective tool required for future target expression and gene therapy in vivo.